PERSEPSI WISATAWAN TERHADAP KEMACETAN DI JALAN PANTAI KUTA KABUPATEN BADUNG BALI - Siringo, Maya; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 2 No 1 (2014): VOL 2, NO 1 (2014): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2014)
Abstract Kuta Beach as a tourist attraction are visited by many tourists, where there are many activities and facilities that cater to tourists, but nevertheless the high level of use of the road on this tourist attraction resulted in congestion problems, therefore it is necessary to study the impact of congestion to provide good service for tourists. Based on the conducted research that revealed two problems, namely how the situation congestion in Kuta Beach? How does the perception of tourists and congestion in Kuta Beach? To uncover problems in the research using primary and secondary data sources, while the type of data used is also quantitative and qualitative data. The methods of collecting data were used through observation, interviews, questionnaires, and literature studies. Sampling technique and analysis of the data were used descriptive qualitative analysis. Congestion occurs because the research results owned roads Kuta Beach and also tourists who want to cross to a place (Kuta beach, restaurants, hotels, and cafes) cause the termination of an activity transportations activities that cause congestion that occurs. The perception of tourists stated that the perception of tourists on the narrow access road in Kuta Beach dominant states is not very good by 27 people (34%), type the perception of congestion problems at Kuta Beach dominant is not well stated 32 people (40%), tourist perception that congestion disturbing activity or work activity trips traveled dominant states are very disturbing as many as 43 people (54%).
Keywords: Keywords: Perception, Guests, Congestion